PKM PENYULUHAN PENCEGAHAN STUNTING PADA MASYARAKAT DESA PULO PANJANG SERANG BANTEN - Maulana, Nova; Wijaya Kusuma, Jaka; Ahmad Faislah, Atmam; Firnanda, Firnanda; Sulistia, Ningrum; Eli Lailatul, Qodariyah (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2024)
Stunting remains a major challenge in many rural areas of Indonesia, including in Pulo Panjang Village. This issue is not only about inhibited physical growth but also impacts the cognitive development of children, which can affect their future. Counseling on stunting is a crucial step in raising community awareness about the importance of early prevention. In this counseling, we focused on practical ways that families and communities can prevent stunting. The results of this program were very encouraging, with many participants showing an increased understanding of stunting and a commitment to changing their lifestyles. This effort demonstrates that with the right knowledge, communities can become more proactive in safeguarding the health of future generations. This counseling is expected to be the starting point for a larger change in Pulo Panjang village